Bringing Science to Law and Policy: Panel Discussion - Bradley Schlaggar; Katie Plax; Susan Block; Timothy McBride; Jill Schupp; Deanna Barch (Washington University Journal of Law & Policy, 2018)
How should law and policy chance, based on our current understanding of brain development? In turn, how can neuroscientists undertake research that would prove most useful in influencing law and policy? Such questions about the intersection of science, law, and policy provided the focus of a transdisciplinary conversations, led by Dr. Deanna Barch. Participants – physicians, an attorney and former Family Court judge, a state legislator, and a health economist – recounted their own experiences and recommendations with a view to bringing traditional divides and actualizing ideas from this conference and symposium, “The Developing Brain.”
Keywords: developmental neurobiology; brain development; Roper v. Simmons; neuroplasticity; adolescence; decision-making; impulse control; youth services; social services; holistic healthcare; child abuse; foster care; mental health services; juvenile delinquency; health policy; CHIP; Medicaid; legislation.